MECHANICAL PROPERTIES OF HIGH-DENSITY POLYETHYLENE (HDPE) WITH TiO2 NANOPARTICLE FILLER PEG 6000 - Sinaga, Sufri; Bukit, Nurdin (EINSTEIN (e-Journal), 2024)
Titanium dioxide (TiO2) is a semiconductor material that has great stability so that it can be utilized as a filler material for High Density Polyethylene (HDPE) thermoplastics. This study was conducted to determine the effect of TiO2 PEG 6000 nanoparticle filler composition on the mechanical properties of HDPE thermoplastics. TiO2 was synthesized with sol gel method and then mixed with PEG 6000. Nanocomposites are made by mixing HDPE with TiO2 nano filler in a rheomixer tool with variations in filler composition (2, 4, 6, 8, 10) %wt, then molded using injection molding tools with ASTM 638 type V standards and analyzing mechanical properties using UTM (Universal Testing Machine) test equipment which includes tensile strength, elongation at break and elastic modulus. The results of XRD analysis produced a particle size of 22nm and SEM tests showed that the surface of TiO2 nanoparticles had a smooth and even surface. The sample with 8% wt filler composition variation is the sample with the best tensile strength value of 84.72 MPa, the highest elongation at break value in the sample with 4% filler of 35.5% and the highest elastic modulus in the sample with 8%wt filler composition of 729.33 MPa.Keywords: Titanium dioxide, HDPE thermoplastic, PEG 6000, Tensile test.